Quantification of Root Growth Patterns From the Soil Perspective via Root Distance Models - Schlüter, Steffen; Blaser, Sebastian R. G. A.; Weber, Matthias; Schmidt, Volker; Vetterlein, Doris (Frontiers in Plant Science, 2018)
The rhizosphere, the fraction of soil altered by plant roots, is a dynamic domain that rapidly changes during plant growth. Traditional approaches to quantify root growth patterns are very limited in estimating this transient extent of the rhizosphere. In this paper we advocate the analysis of root growth patterns from the soil perspective. This change of perspective addresses more directly how certain root system architectures facilitate the exploration of soil. For the first time, we propose a parsimonious root distance model with only four parameters which is able to describe root growth patterns throughout all stages in the first 3 weeks of growth of Vicia faba measured with X-ray computed tomography. From these models, which are fitted to the frequency distribution of root distances in soil, it is possible to estimate the rhizosphere volume, i.e., the volume fraction of soil explored by roots, and adapt it to specific interaction distances for water uptake, rhizodeposition, etc. Through 3D time-lapse imaging and image registration it is possible to estimate root age dependent rhizosphere volumes, i.e., volumes specific for certain root age classes. These root distance models are a useful abstraction of complex root growth patterns that provide complementary information on root system architecture unaddressed by traditional root system analysis, which is helpful to constrain dynamic root growth models to achieve more realistic results.